MENINGKATKAN HASIL BELAJAR PKn MELALUI PENERAPAN METODE TANYA JAWAB DENGAN FARIASI MEDIA PEMBELAJARAN PADA POKOK BAHASAN MASYARAKAT MADANI DI KELAS XI IPS1 SMA NEGERI 10 PEKANBARU - Darmali, Darmali (Perspektif, 2017)
This research is based on the low percentage of achievement on the MinimumExhaustiveness Criteria that was given by the students of grade XI 1 SOCIAL 10SENIOR HIGH SCHOOL Pekanbaru, school year 2015/2016 From the number ofstudents 42 people who took the post test on the teaching materials Characteristic ofcivil society with Cooperative learning model, only 15 people can be passed (36.%)and the rest about 27 people are declared not graduated (64,%). The data indicate thatthe learning outcomes in these teaching materials can be declared unfinished. Thedisagreement is evident from the proof of the percentage of all students graduationonly reached 36,%. The percentage is far from the ideal percentage between 80% -100%. Even the percentage of graduation is smaller than the percentage of nongraduation.Therefore, for such cases it is necessary to hold a classical remedial. Theprocess of classical remedial in this case the author did through classroom actionresearch activities.